Parvimonas micra promotes colorectal tumorigenesis and is associated with prognosis of colorectal cancer patients - Zhao, Liuyang; Zhang, Xiang; Zhou, Yunfei; Fu, Kaili; Lau, Harry Cheuk-Hay; Chun, Tommy Wai-Yiu; Cheung, Alvin Ho-Kwan; Coker, Olabisi Oluwabukola; Wei, Hong; Wu, William Ka-Kei; Wong, Sunny Hei; Sung, Joseph Jao-Yiu; et al. (Oncogene, 2022)
Large-scale fecal shotgun metagenomic sequencing revealed the high abundance of Parvimonas micra in colorectal cancer (CRC) patients. We investigated the role and clinical significance of P. micra in colorectal tumorigenesis. The abundance of P. micra was examined in 309 fecal samples and 165 colon biopsy tissues of CRC patients and healthy subjects. P. micra was significantly enriched in fecal samples from 128 CRC patients compared to 181 healthy subjects ( P < 0.0001); and in colon tissue biopsies from 52 CRC patients compared to 61 healthy subjects ( P < 0.0001). Multivariate analysis showed that P. micra is an independent risk factor of poor survival in CRC patients (Hazard Ratio: 1.93). P. micra strain was isolated from feces of a CRC patient. Apc min/+ mice gavaged with P. micra showed significantly higher tumor burden and tumor load (both P < 0.01). Consistently, gavage of P. micra significantly promoted colonocyte proliferation in conventional mice, which was further confirmed by germ-free mice. P. micra colonization up-regulated genes involved in cell proliferation, stemness, angiogenesis and invasiveness/metastasis; and enhanced Th17 cells infiltration and expression of Th17 cells-secreted cytokines (Il-17, Il-22, and Il-23) in the colon of Apc min/+ , conventional and germ-free mice. P. micra -conditioned medium significantly promoted the differentiation of CD4 + T cells to Th17 cells (IL-17 + CD4 + phenotype) and enhanced the oncogenic Wnt signaling pathway. In conclusion, P. micra promoted colorectal tumorigenesis in mice by inducing colonocyte proliferation and altering Th17 immune response. P. micra may act as a prognostic biomarker for poor survival of CRC patients.